2022
DOI: 10.1007/s12529-021-10052-8
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model of Compliance with COVID-19 Prescriptions: Instrumental, Normative, and Affective Factors Associated with Health-Protective Behaviors

Abstract: Background The efficacy of public measures for reducing the transmission of the COVID-19 infection relies on citizens’ voluntary adherence with prescribed actions. Drawing on prior literature about compliant behavior, this study aimed to identify factors associated with people engagement in health-protective behaviors by including a conjoint complement of instrumental/self-oriented, normative/community-based, and affective variables. Method A cross-sectional study invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
0
13
0
2
Order By: Relevance
“…Lastly, the perception of susceptibility to COVID‐19 may have overwhelmed citizens, impacting their current concerns and ability to rather focus on the foreseen opportunities for personal growth (Barni et al, 2020 ; Fiorillo et al, 2020 ; Prati & Mancini, 2021 ; Rochira et al, 2022 ). Thus, the perception of susceptibility to COVID‐19 was taken into account as a control variable at both individual (i.e., knowing someone who got infected with COVID‐19) and province (i.e., the severity of local COVID‐19 impact, as reported by the Istat and Iss report, 2020 ) levels.…”
Section: Rationale For the Studymentioning
confidence: 99%
“…Lastly, the perception of susceptibility to COVID‐19 may have overwhelmed citizens, impacting their current concerns and ability to rather focus on the foreseen opportunities for personal growth (Barni et al, 2020 ; Fiorillo et al, 2020 ; Prati & Mancini, 2021 ; Rochira et al, 2022 ). Thus, the perception of susceptibility to COVID‐19 was taken into account as a control variable at both individual (i.e., knowing someone who got infected with COVID‐19) and province (i.e., the severity of local COVID‐19 impact, as reported by the Istat and Iss report, 2020 ) levels.…”
Section: Rationale For the Studymentioning
confidence: 99%
“…It is interesting that, although the sense of community was negatively predicted by levels of hopelessness, it did not appear to be associated with COVID-19 denialism. Conversely, previous studies have reported that a feeling of belongingness and attachment to a place, accompanied by a sense of connection with other members of the community, could promote adherence to norms and prosocial behaviours [ 27 , 40 , 41 , 42 , 43 ]. Although the concept of a sense of community is generally analysed by referring to a geographically defined community, it is possible that a sense of belonging and a connection to one’s city are not sufficient to explain the complex phenomenon of denialism.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with previous empirical and validation studies, the results showed a one-factor model for SoC Mannarini et al, 2020) and SoC-R (Prati et al, 2020), as well as for the effectiveness of institutional response (Compare et al, 2021) and reflexivity. Two first-order factors emerged for current personal and social concerns (Rochira et al, 2021) and for perceptions of a postpandemic future (i.e., personal growth and return to pre-COVID life). Current personal and social concerns, perceptions of a postpandemic future, seen as restoring life as it was before the pandemic or as personal growth were entered as separate dimensions in the model (see Figure 1).…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…Respondents indicated their level of concern about the impact of the COVID-19 pandemic on their personal safety and on society at large. The eight ad-hoc items derived from the main findings of the Brooks et al's (2020) review, investigated concerns about how COVID-19 affected their safety (personal concerns, five items, e.g., "The possibility of being infected") and society at large (social concerns, three items, e.g., "The possibility of the economic downturn because of inactive time") (Rochira et al 2021). Respondents rated on a 5-point Likert scale ranging from 1 (nothing) to 5 (at all) how concerned they were about what was stated in each item.…”
Section: Current Personal and Social Concernsmentioning
confidence: 99%
See 1 more Smart Citation